Laboratory performance study for passive sampling of nonpolar chemicals in water - Booij, Kees; Smedes, Foppe; Crum, Steven (Environmental toxicology and chemistry, 2017)
Two laboratory performance studies with 21 and 11 participants were carried out for passive sampling of nonpolar chemicals in water, using silicone samplers that were deployed for 7 wk and 13 wk at 2 river sites in the Netherlands. Target analytes were polychlorinated biphenyls, polycyclic aromatic hydrocarbons (PAHs), polybrominated diphenyl ethers (PBDEs), hexachlorobutadiene, hexachlorobenzene, and a number of performance reference compounds (PRCs). Calculation of aqueous concentrations based on prescribed input values and a prescribed uptake model was also included. Between-laboratory coefficients of variation (CVs) in the analysis of target compounds were approximately 20% at concentrations of 100 ng g-1 and approximately 100% at concentrations of 0.01 ng g-1 , which was similar to previous results for the analysis of biota samples. The analysis of PRCs yielded water sampling rates with a between-laboratory CV of 18% to 30%. The sampling rate model showed a nearly perfect match with the consensus values of retained PRCs. The implications of the present study for future interlaboratory exercises are discussed. Environ Toxicol Chem 2017;36:1156-1161. © 2016 SETAC.
Keywords: monitorování životního prostředí; hexachlorbenzen; Proficiency testing; polychlorované bifenyly; Netherlands; halogenované difenylethery; Environmental Monitoring; teoretické modely; Passive sampler; Interlaboratory study; polycyklické aromatické uhlovodíky; řeky; Models, Theoretical; Rivers; chemické látky znečišťující vodu; Hexachlorobenzene; Polychlorinated Biphenyls; Quality assurance; Water Pollutants, Chemical; Polycyclic Aromatic Hydrocarbons; Halogenated Diphenyl Ethers; Organic contaminants; Analytical chemistry; Nizozemsko